INCOMPLETENESS ANALYSIS OF FILLING IN THE SUMMARY OF DISCHARGE OF INPATIENTS AT LAWANG MEDIKA HOSPITAL, MALANG REGENCY, EAST JAVA PROVINCE - Tiara Kelana Zahrotunnisa; Panca Radono (Journal of Hospital Management and Services, 2025)
The discharge summary form has an important function for the claims process and the follow-up treatment required by patients in the hospital. The purpose of this study is to find out the cause of the incomplete filling of the summary of the discharge of inpatients at Lawang Medika Hospital, Malang Regency, East Java Province. The method in this study is qualitative descriptive. The data analysis carried out is data reduction, data presentation and conclusion drawn. The data validity test in this study is Data Triangulation. The policy in returning the incomplete return summary has not been implemented by the medical record officer because it focuses on the number of return medical record documents which are then given to the unit in charge of the claim process. Based on the results of the study, it is concluded that the four elements that can cause incompleteness in filling out the discharge summary must be evaluated and followed up so as not to hinder in providing services to patients at Lawang Medika Hospital.